Casting versus flexible intramedullary nailing in displaced forearm shaft fractures in children aged 7-12 years: a study protocol for a randomised controlled trial - Grahn-Shahar Petra M; Sinikumpu Juha-Jaakko; Nietosvaara Yrjänä; Syvänen Johanna; Salonen Anne; Ahonen Matti Helenius Ilkka (BMJ PUBLISHING GROUP, 2022)
Introduction The forearm is the most common fracture location in children, with an increasing incidence. Displaced forearm shaft fractures have traditionally been treated with closed reduction and cast immobilisation. Diaphyseal fractures in children have poor remodelling capacity. Malunion can cause permanent cosmetic and functional disability. Internal fixation with flexible intramedullary nails has gained increasing popularity, without evidence of a better outcome compared with closed reduction and cast immobilisation.Method and analysis This is a multicentre, randomised superiority trial comparing closed reduction and cast immobilisation to flexible intramedullary nails in children aged 7-12 years with >10 degrees of angulation and/or >10 mm of shortening in displaced both bone forearm shaft fractures (AO-paediatric classification: 22D/2.1-5.2). A total of 78 patients with minimum 2 years of expected growth left are randomised in 1:1 ratio to either treatment group. The study has a parallel non-randomised patient preference arm. Both treatments are performed under general anaesthesia. In the cast group a long arm cast is applied for 6 weeks. The flexible intramedullary nail group is immobilised in a collar and cuff sling for 4 weeks. Data are collected at baseline and at each follow-up until 1 year.Primary outcome is (1) PROMIS paediatric upper extremity and (2) forearm pronation-supination range of motion at 1-year follow-up. Secondary outcomes are Quick DASH, Paediatric Pain Questionnaire, Cosmetic Visual Analogue Scale, wrist and elbow range of motion as well as any complications and costs of treatment. We hypothesise that flexible intramedullary nailing results in a superior outcome.Ethics and dissemination We have received ethical board approval (number: 78/1801/2020) and permissions to conduct the study from all five participating university hospitals. Informed consent is obtained from the parent(s). Results will be disseminated in peer-reviewed publications.